Analisis Penerapan PSAK 30 Dalam Penyajian Laporan Keuangan Lessor - Saputra, Permana; Rosita, Siti Ita (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
This study aims to determine the system of financing, recording, and presentation of lease accounting contracts applied by the company whether it has been in accordance with the statement of financial accounting standards 30. The results of the research show that in its operational activities the company uses the method of financing lease, because in the lease contract the company transfers substantially all the risk and rewards associated with the ownership of the asset. In the contract the company recognizes assets in the from of finance lease receivables in the amount equal to the net rental ivestment. The receivables from rental receivablesare treated as principal payments which will be presented in the statement of financial position and the finance lease income to be presented in the statement of income. In general, the accounting of the company’s lease transactions in conformity with the statement of financial accounting standart 30 which has been described in the noted to the financial statements of the company. With the provisions of accounting for leases (PSAK 73) that have been retified by DSAK-IAI, in 2017 effective as of 1 Januari 2019, the company should consider the provisions in the application of the rental accounting policy in the subsequent period. Keywords: finance lease, financial statement, PSAK 30